2021
DOI: 10.1002/mrm.28645
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of CSF transport using high spatiotemporal resolution dynamic contrast‐enhanced MRI in mice: Effect of anesthesia

Abstract: Purpose Dynamic contrast‐enhanced MRI (DCE‐MRI) represents the only available approach for glymphatic cerebrospinal fluid (CSF) flow 3D mapping in the brain of living animals and humans. The purpose of this study was to develop a novel DCE‐MRI protocol for mapping of the glymphatic system transport with improved spatiotemporal resolution, and to validate the new protocol by comparing the transport in mice anesthetized with either isoflurane or ketamine/xylazine. Methods The contrast agent, gadobutrol, was admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 50 publications
4
78
1
Order By: Relevance
“…Note that prior studies computed enhancement factors based on oscillatory (zero mean) flow ( 64, 65 ), whereas our calculations are based on steady (nonzero mean) flow, which we have previously argued is more effective for dispersive transport ( 19, 63 ). Although Taylor dispersion in pial PVSs is unlikely to account for the entirety of tracer transport observed in experiments, these estimates generally suggest that Intermediate scenario 1 with small precapillary PVSs (Γ precap = 0.07) is the only scenario with sleep/awake variations in volume flow rate large enough to explain tracer transport reported in several experiments ( 5, 51, 52, 61 ).…”
Section: Discussionmentioning
confidence: 85%
“…Note that prior studies computed enhancement factors based on oscillatory (zero mean) flow ( 64, 65 ), whereas our calculations are based on steady (nonzero mean) flow, which we have previously argued is more effective for dispersive transport ( 19, 63 ). Although Taylor dispersion in pial PVSs is unlikely to account for the entirety of tracer transport observed in experiments, these estimates generally suggest that Intermediate scenario 1 with small precapillary PVSs (Γ precap = 0.07) is the only scenario with sleep/awake variations in volume flow rate large enough to explain tracer transport reported in several experiments ( 5, 51, 52, 61 ).…”
Section: Discussionmentioning
confidence: 85%
“…In particular, Xie et al showed K-X to mimic natural sleep with respect to glymphatic activity [ 10 ]. Stanton et al recently confirmed that contrast transport pathways differ between isoflurane and K-X anesthetic regimes [ 71 ]. Specifically, parenchymal penetration is poorer using isoflurane due to rapid efflux of contrast agent into the spinal canal and along cranial nerve sheaths.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that these numerous links between the skull marrow and the dura enable not only cell traffic towards the meninges ( 4 ) but also bidirectional crosstalk. We therefore implemented a 2-photon intravital microscopy (IVM) and ex vivo imaging pipeline to visualize CSF distribution after fluorescent tracer injection into the cisterna magna ( 9, 10 ). Intracisternal injection of 70 kD FITC-labeled ovalbumin was combined with intravenous labeling of the blood pool using 70 kD Texas red-labeled dextran.…”
Section: Resultsmentioning
confidence: 99%